Desenvolvimento de biossensor óptico para detecção de microrganismos patogênicos - Thomazini, Bruno da Silva (2016)
Infections caused by super-resistant microorganisms represent a major clinical and fiscal burden as a global problem. In addition, microorganisms are responsible for the deterioration of foods that, if consumed, can cause great harm to consumer health. For this reason, there is a need for constant monitoring both in the health area and in industrial processes, in order to prevent infections from occurring. Conventional methods for detecting micro-organisms are based on specific biological and biochemical identification. Although these methods are sensitive, inexpensive, and provide quantitative and qualitative information regarding the nature of the microorganism, they are restricted because they require relatively long time and require initial sample treatment for pathogens at low concentrations. The use of peptides in the detection of pathogenic microorganisms has been the subject of studies since it allows a precise and rapid detection. Peptides are known antimicrobial components used for a long time in the fight against infections caused by pathogens. Previous studies have demonstrated that the polycerradin peptide can be used in the development of sensors, since its antimicrobial action inhibits the luminescence of microorganisms due to cell death. The light signals from the antimicrobial action of this peptide against the microorganism were analyzed for the microorganisms Escherichia coli, Staphylococcus aureus, Enterococcus faecalis, Shigela sonnei, Furasim subglutinans, Colletotrichium gloeosporioides e Candida albicans. The spectra obtained through the data, which were collected by photoluminescence spectroscopy, showed that there was suppression of the luminescence around λ = 700-750 nm, when the lipopeptide extract (ELP) was added in all evaluated microorganisms. Thus, it was possible to determine the antimicrobial action of this peptide against the microorganisms studied, as well as the presence of these microorganisms through its emission spectrum. This technique was applied in the development and construction of an optical sensor, using materials of low cost, for use in the monitoring and identification of pathogenic microorganisms in several areas, such as health and food industry.